RESILIENSI KAPASITAS ANGGARAN DAERAH: PENGUKURAN PADA KONDISI PANDEMI COVID-19 - indriani, Ika kurnia; Cahyowati, Anik; widodo, Agus (MEASUREMENT : Jurnal Program Studi Akuntansi, 2025)
The most significant factor in managing COVID-19 cases is the local budget capacity. The local government will be able to effectively implement strategic programmes during the COVID-19 epidemic while also sustaining regional economic growth, especially to its significant fiscal capacity. The budget capacity assessment attempts to examine the capacity of municipal governments in Indonesia to effectively administer the APBD. The assessment of budget capacity resilience employ a descriptive quantitative methodology involving measures such as budget solvency, financial independence, and service-level solvency. The assessment results indicate that the municipalities of Mataram, Tidore, Batam, and Sabang achieved the greatest budget capacity index. The government with the highest ranking possesses the capacity to effectively manage unprecedented crises like the COVID-19 pandemic. Meanwhile, the municipalities of Bengkulu, Bontang, and Tegal have the lowest budget capacity index.